2000
DOI: 10.2190/1yud-y451-6yed-81xn
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dual Credit Programs on College Students' Integration and Goal Attainment

Abstract: This study was designed to investigate the differences in integration and goal achievement between students entering college with and without credits from a dual credit program. Dual credit programs included in this study were Saint Louis University's Advanced College Credit 1818 Program (ACC) and Advanced Placement Testing (AP). The results of the logistic regressions indicated that ACC credits significantly influenced students' ability to persist and graduate. The results of the linear regressions indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Early studies of dual enrollment matched students along few dimensions An (Perkings & Windham, 2002;Spurling & Gabriner, 2002). More recent studies considered multiple factors that influence a student's selection into dual enrollment (Delicath, 1999;Karp et al, 2007;Kim & Bragg, 2008;Morrison, 2008;Swanson, 2008). Although these studies improve on earlier research, dual enrollees may continue to differ from non-dual enrollees in ways that are unknown to the researcher.…”
Section: The Equity Agenda Of Dual Enrollmentmentioning
confidence: 99%
“…Early studies of dual enrollment matched students along few dimensions An (Perkings & Windham, 2002;Spurling & Gabriner, 2002). More recent studies considered multiple factors that influence a student's selection into dual enrollment (Delicath, 1999;Karp et al, 2007;Kim & Bragg, 2008;Morrison, 2008;Swanson, 2008). Although these studies improve on earlier research, dual enrollees may continue to differ from non-dual enrollees in ways that are unknown to the researcher.…”
Section: The Equity Agenda Of Dual Enrollmentmentioning
confidence: 99%
“…According to Eimers and Mullen (2003), students who entered college with either advanced placement (AP) or concurrent enrollment credits displayed a higher retention rate than students who entered with no previous credits. Additionally, Delicath (1999) found both concurrent enrollment credit and AP credit positively correlated with student retention into the sophomore year of college.…”
Section: Introductionmentioning
confidence: 92%
“…In light of deficiencies in student performance among high school students nationally and in Kentucky, research has shown dual credit courses to provide a rigorous curricular alternative to the traditional high school curriculum (Windham, 1998;Delicath, 1999;Hanson, 2001;. The research examined in this study clearly demonstrates the value of a strong academic curriculum on student success in postsecondary education school (Adelman, 1999;Horn, Kojaku, & Carroll, 2001;Alexander & Pallas, 1984).…”
Section: Significance Of the Studymentioning
confidence: 73%
“…Dual credit courses invigorate the curriculum for high school students (Windham, 1998;Delicath, 1999;Hanson, 2001;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation